Dentoskeletal Effects of Multi P® Prefabricated Functional Appliance on Class II Div I Children in Late Mixed Dentition - Chalipa, Javad; Fallahinejad Ghajari, Masoud; Vahid Golpayegani, Mojtaba; Mohaveri, Mostafa; Jafary, Maral (Journal of Dental School, 2019)
Objectives: Prefabricated functional appliances have therapeutic effects similar to those of custom-made functional appliances. This study aimed to assess the dentoskeletal effects of Multi P® prefabricated functional appliance on Class II Div 1children in late mixed dentition. Methods: This open label trial was conducted on 18 children aged 9-12 years with Cl II Div 1 malocclusion due to mandibular deficiency during a 9-month period. Written informed consent was obtained from the parents. Multi P ® (RMO, Strasbourg, France) was used by the patients 4 hours/day and overnight (minimum of 8 hours) in conjunction with specific exercises (pressing the teeth in the recorded occlusion, pressing the tongue against the palate and uninostril breathing). Patients were visited monthly. Study casts and cephalometric radiographs were obtained before and after the treatment. Data were analyzed using paired samples t-test and McNemar’s test. Results: The Go-Gn (P=0.029) and Me-N (P=0.021) distances significantly increased following the use of appliance while overjet (P<0.0001), absolute overbite (P=0.002) and the Wits appraisal (P=0.019) significantly decreased. Other understudy angles did not change significantly. Conclusion: Multi P® appliance decreases the jaw base discrepancy and corrects the overjet and overbite.